Proceedings of GeoShanghai 2018 International Conference: Geoenvironment and Geohazard (Springer Singapore, 2018)
This book is the seventh volume of the proceedings of the 4th GeoShanghai International Conference that was held on May 27 - 30, 2018. This volume, entitled "Geoenvironment and Geohazards", presents the recent advances and technology in geoenvironmental engineering and geohazards. The state-of-the-art theories, methodologies and findings in the related topics are included. This book may benefit researchers and scientists from the academic fields of soil & rock mechanics, geotechnical engineering, geoenvironmental engineering, transportation engineering, geology, mining and energy, as well as practical engineers from the industry.